The CRL4DCAF1 cullin‐RING ubiquitin ligase is activated following a switch in oligomerization state. (30th September 2021) - Mohamed, Weaam I; Schenk, Andreas D; Kempf, Georg; Cavadini, Simone; Basters, Anja; Potenza, Alessandro; Abdul Rahman, Wassim; Rabl, Julius; Reichermeier, Kurt; Thomä, Nicolas H
Abstract: The cullin‐4‐based RING‐type (CRL4) family of E3 ubiquitin ligases functions together with dedicated substrate receptors. Out of the ˜29 CRL4 substrate receptors reported, the DDB1‐ and CUL4‐associated factor 1 (DCAF1) is essential for cellular survival and growth, and its deregulation has been implicated in tumorigenesis. We carried out biochemical and structural studies to examine the structure and mechanism of the CRL4 DCAF1 ligase. In the 8.4 Å cryo‐EM map of CRL4 DCAF1, four CUL4‐RBX1‐DDB1‐DCAF1 protomers are organized into two dimeric sub‐assemblies. In this arrangement, the WD40 domain of DCAF1 mediates binding with the cullin C‐terminal domain (CTD) and the RBX1 subunit of a neighboring CRL4 DCAF1 protomer. This renders RBX1, the catalytic subunit of the ligase, inaccessible to the E2 ubiquitin‐conjugating enzymes. Upon CRL4 DCAF1 activation by neddylation, the interaction between the cullin CTD and the neighboring DCAF1 protomer is broken, and the complex assumes an active dimeric conformation. Accordingly, a tetramerization‐deficient CRL4 DCAF1 mutant has higher ubiquitin ligase activity compared to the wild‐type. This study identifies a novel mechanism by which unneddylated and substrate‐free CUL4 ligases can be maintained in an inactive state. Synopsis: Cullin‐RING ubiquitin ligases are known to be regulated by neddylation or at the level of substrate recognition. Here, cryo‐EM reconstructions of the human CUL4‐RBX1‐DDB1‐DCAF1 (CRL4 DCAF1 ) reveals a novel mechanism based on oligomerization state switch between tetrameric and dimeric complexes. Cryo‐EM models show CRL4 DCAF1 as a tetrameric, auto‐inhibited complex, in which E2 enzyme access is blocked. The auto‐inhibited CRL4 DCAF1 tetramer switches to a dimeric active conformation upon neddylation. Arg‐1247 mutation in the WD40 domain of DCAF1 causes disassembly of the tetrameric complex into a dimer, and exhibits higher catalytic activity towards the viral DCAF1 substrate VPR‐UNG2. A cryo‐EM map of NEDD8‐CRL4 DCAF1 bound to the COP9‐signalosome shows the neddylated complex in a dimeric conformation. Abstract : Cullin‐RING ubiquitin ligases are known to be regulated by neddylation or at the level of substrate recognition. Here, cryo‐EM reconstructions of the human CUL4‐RBX1‐DDB1‐DCAF1 (CRL4 DCAF1 ) reveals a novel mechanism based on oligomerization state switch between tetrameric and dimeric complexes.